Teacher collaboration, differing expectations, and emotions in school improvement: "It's always take, take, take". Issue 4 (21st October 2019) - Weddle, Hayley; Lockton, Marie; Datnow, Amanda
Abstract : Purpose: While the benefits of teacher collaboration are well documented, less is known about how emotions intersect with teachers' collective work. Educational change is an emotional process, as reform efforts often involve shifts in teachers' daily routines and professional identities. To better understand these complexities, the purpose of this paper is to investigate the emotional dimensions of teachers' collaborative efforts to improve instruction. Design/methodology/approach: Drawing on qualitative data, this longitudinal case study of one teacher team explores how teacher collaboration for instructional improvement intersects with emotional geographies. Data analyzed include three years of meeting observations and annual interviews with teachers and school leaders. Findings: An analysis of data reveals how emotions both shaped and were shaped by teachers' collaboration experiences. Varying beliefs about practice, expectations about collective work and identity (in this case, gender) impacted collaboration and subsequently opportunities for instructional improvement. Practical implications: This study demonstrates how attending to the emotional aspects of teacher collaboration could serve as an effective strategy for bolstering capacity-building efforts. Findings highlight the interplay between emotional geographies, suggesting that common ground across one geography could potentially be built upon to close gaps across others. Originality/value: This study provides a unique longitudinal exploration of the emotional dimensions of teachers' collective work. The study also contributes to new knowledge about the ways in which teachers' emotions and collaborative experiences intersect, including the interplay between emotional geographies.